Altruism in organ donation: an unnecessary requirement?. Issue 2 (28th March 2013) - Moorlock, Greg; Ives, Jonathan; Draper, Heather
Abstract : Altruism has long been taken to be the guiding principle of ethical organ donation in the UK, and has been used as justification for rejecting or allowing certain types of donation. We argue that, despite this prominent role, altruism has been poorly defined in policy and position documents, and used confusingly and inconsistently. Looking at how the term has been used over recent years allows us to define 'organ donation altruism', and comparing this with accounts in the philosophical literature highlights its theoretical shortcomings. The recent report from the Nuffield Council on Bioethics reaffirmed the importance of altruism in organ donation, and offered a clearer definition. This definition is, however, more permissive than that of altruism previously seen in UK policy, and as a result allows some donations that previously have been considered unacceptable. We argue that while altruistic motivation may be desirable, it is not necessary.